Case report: a precancerous lesion associated with HPV in the anal canal diagnosed by magnifying endoscopy with narrow-band imaging and resected by endoscopic submucosal dissection - Li, Hengcun; Sun, Xiujing; Yang, Ling; Xu, Rui; Li, Peng (Frontiers in Medicine, 2023)
Although anal cancer remains rarely diagnosed in the world, its frequency is rising, especially in high-risk groups. The prognosis of advanced anal cancer is poor. However, there are still few reports on the endoscopic diagnosis and treatment of early anal cancer and its precancerous lesions. A 60-year-old woman was referred to our hospital for endoscopic treatment of a flat precancerous lesion in the anal canal, which was identified by narrow-band imaging (NBI) and confirmed by pathological examination in another hospital. The pathological results showed a high-grade squamous intraepithelial lesion (HSIL) in the biopsy specimen, and immunochemistry staining showed P16 positive, suggesting HPV infection. We performed pre-resection endoscopic examination for the patient. A lesion with a clear margin and tortuous dilated vessels was revealed under magnifying endoscopy with NBI (ME-NBI), which stayed unstained after iodine spraying. The lesion was successfully removed en bloc using ESD without complications, and the resected specimen was a low-grade squamous intraepithelial lesion (LSIL) with positive immunochemistry staining of P16. The patient underwent follow-up coloscopy a year after ESD, and the anal canal healed well with no suspicious lesions found. From this case, we can learn that ESD is safe and effective for curative resection of precancerous lesions of the anal canal.